Reference values for the six-minute walk test in obese Indian population - Dosi, Ravi; Songara, Ashwin; Joshi, Prakash; Jain, Arpit; Solanki, Awadesh P.S. (International Journal of Research in Medical Sciences, 2017)
Background: The six-minute walk test is one of the most powerful test used to measure the functional capacity in various chronic conditions such as in Obesity. There are very few reported studies on SMWT on Obese population all over the world, and there is no reference equation for SMWD. The aim of present study is to propose a Reference equation which could predict the distance walked in SMWT by obese individuals. Methods: 150 obese individuals free from any cardiorespiratory disease were randomized into 2 groups. SMWT data from group A was used to propose the reference equation and SMWD for Group B was predicted. Significance of difference between predicted and original values for group B was found. Results: Mean SMWD for Group A was 304.56 (SD= 68.28) which significantly correlated to (by using linear regression method) age (r = -0.32, p <0.001), BMI (r = -0.43, p <0.001) SpO2* (r=-0.35, p<0.001). These could explain 56% of the total variance in 6MWT. Though the difference between predicted and original values for group B wasn’t found to be statistically significant. The proposed Reference equation is: 6MWT distance = (6.8) O2 saturation-(4.3) BMI-(0.6) age-170.64. Conclusions: SMWT is a simple, safe and powerful test to assess the functional status. The standardized SMWD values for Indian obese population would serve as benchmark to assess baseline functional capacity, prescribe proper and safe exercise intensity and monitor changes after rehabilitation interventions.